Non-indigenous freshwater fish research in Greece: Current status and future prospects - KOUTSIKOS, NICHOLAS; ZOGARIS, STAMATIS; VARDAKAS, LEONIDAS; KALANTZI, OLGA-IOANNA (Mediterranean Marine Science, 2021)
Many studies around the globe have documented that the introduction of non-indigenous fish species (NIFS) may pose severe impacts on native biota, ecosystem functioning, and ecosystem services. In Greece, publications on NIFS have increased in recent decades, however, review studies of past and current scientific research on freshwater NIFS in the country are currently lacking. Τhe aim of the present study was to: (a) assess the current state of knowledge of freshwater NIFS in Greece based on the existing scientific literature, (b) evaluate well-studied areas of NIFS research, and (c) identify important gaps that may direct national authorities to implement appropriate research, management and conservation actions reversing the negative impacts of NIFS. A systematic literature review on NIFS research within Greek inland waters was performed by applying the PRISMA methodology (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). Overall, our initial search resulted in 2,794 published articles, 87 of which met our selection criteria and were thus included for full analysis. Evidently, NIFS failed to attract the interest of ecologists in Greece until the turn of the century, at which point, publications increased at a rapid rate. However, the majority of the studies were mainly monothematic concerning NIFS distribution within freshwater ecosystems of Greece (37%), followed by studies on ecological and biological aspects of NIFS (28%). Studies based on fieldwork and laboratory experiments were by far the most common type of research, followed by studies based on bibliographic data. Despite the fact that almost half of the publications were field observational studies, most of them used only qualitative data (plain presence/absence data). Critical aspects of impact assessment were missing; 84% of the reviewed studies did not provide any concrete evidence of NIFS impacts to native biota. Overall, the focus of the studies was uneven, with important gaps in areas of theoretical and practical importance for policy-relevant detection, control, and management of NIFS. Findings may assist researchers in filling scientific gaps identified by our review and guide authorities to define national priorities to prevent and control the spread of NIFS within the country.